ANALISIS KRITIS PROBLEMATIKA HAK BERAGAMA DAN BERKEYAKINAN DALAM KEBIJAKAN PENDIDIKAN AGAMA DI INDONESIA - Ach. Nurholis Majid (Reflektika, 2020)
Religiosity is an essential entity of Indonesian society. Only 0.04% of Indonesians do not choose official religion. This religious fact gives the government confidence that religion is determinant in the lives of Indonesian people. Then, the government poured that belief in the Law on the National Education System (No. 20/2003) Article 12 Section 1a. But then it ran into a problematic crucial. Incorporating religion in education can provide hope for social cohesion and become a cornerstone of morality. Still, on the other hand, it can be a laboratory for the transmission of extremism.  Therefore, the state policy in SISDIKNAS Article 12 Section 1a needs to be evaluated critically to understand and describe the substance of the policy, implementation, and impact, both planned and unplanned. For this purpose, this article tries to browse the literature to obtain the required data. This research provides some images. First, the Law generally has a positive substance but is very prone to causing social and legal problems caused by disproportionate and dilemmas derivatives of regulation. Second, the policy of religious rights and belief in the scope of education has not entirely led to the inclusive meaning of religion, resulting in several violations of human rights to the practice of exclusivism. Third, the orientation of religious significance can be the spirit of Indonesian national education.